Inotropic Therapy in Newborns, A Population-Based National Registry Study*. Issue 10 (October 2016) - Burns, Margrete Larsen; Stensvold, Hans Jørgen; Risnes, Kari; Guthe, Hans Jørgen; Astrup, Henriette; Nordhov, S. Marianne; Selberg, Terje Reidar; Rønnestad, Arild; Lang, Astri Maria
Abstract : Objective: To describe the use of inotropic drugs and the characteristics of neonates receiving such treatment in a national cohort of patients admitted to neonatal ICUs in Norway. Design: A national registry study of patients included in the Norwegian Neonatal Network database 2009–2014. Demographic and treatment data, including the use of inotropic drugs (dopamine, dobutamine, epinephrine, norepinephrine, milrinone, and levosimendan) and outcomes, were retrieved and analyzed. Setting: Neonatal ICUs in Norway. Patients: All patients admitted to Norwegian neonatal ICUs 2009–2014 with a postmenstrual age of less than 310 days at admission, corresponding to a postnatal age of less than 28 days for a child born at term ( n = 36 397). Interventions: None. Measurements and Main Results: Inotropic drugs were administered to 974 of 361, 803 live born infants (0.27%) in the study period, representing 2.7% of the neonatal ICU patient population. The relative proportion of neonatal ICU patients receiving inotropes decreased with increasing gestational age, yet 41% of the patients receiving inotropes were born at term. Of note, 89.8% of treated patients received dopamine. Use of inotropes was particularly prevalent in patients with necrotizing enterocolitis (72.4%) and pulmonary hypertension (42.1%) and in patients with gestational age less than 28 weeks (28.2%). Inotropic treatment initiated in the first week of life (84.2%) was associated with birth asphyxia and pulmonary hypertension, whereas treatment initiated after the first week of life was associated with extremely preterm birth, neonatal surgery, neonatal sepsis, cardiac disease, and necrotizing enterocolitis. Conclusions: This comprehensive epidemiologic study indicates that less than 0.3% of newborns receive inotropic support in the neonatal period. Dopamine was the most commonly used drug. Relating inotrope use to clinical condition, gestational age, and postnatal age may be useful for clinicians and helpful in delineating relevant patient populations for future clinical trials.